Probing the Water Vapor Adsorption Properties of MIL‐101 Doped with Manganese. Issue 9 (18th October 2021) - Liu, Shang; Wu, Ping; Zhang, Shiping; Fu, Guodong; Yan, Dan; Han, Xiaoli; Huai, Xiulan; Xu, Min
Abstract: The chemical heat pump system is a heat management system based on the steam cycle. Combining the heat pump material and porous material into a frame can improve the heat storage capacity of the system. Metal‐OrganicFrameworks (MOF) is a kind of porous material with high porosity and specific surface area. We selected MIL‐101 (Cr) and studied whether doping can improve its water vapor adsorption capacity. In the hydrothermal synthesis process, we added manganese nitrate and chromium nitrate with different molar ratios to prepare four kinds of doped samples with diverse manganese contents, which were characterized by SEM, nitrogen adsorption test, XRD, FTIR, Raman test, TG, and water vapor adsorption test. Compared with the undoped sample, the particle diameter of the doped sample was doubled, and the water vapor adsorption increased by 30 %. Our experiments show that doping manganese ions is an effective way to adjust particle size and increase adsorption capacity. Abstract :